Autoimmune liver disease, autoimmunity and liver transplantation - Carbone, Marco; Neuberger, James M. (Journal of hepatology, 2014)
Primary biliary cirrhosis (PBC), primary sclerosing cholangitis (PSC) and autoimmune hepatitis (AIH) represent the three major autoimmune liver diseases (AILD). PBC, PSC, and AIH are all complex disorders in that they result from the effects of multiple genes in combination with as yet unidentified environmental factors. Recent genome-wide association studies have identified numerous risk loci for PBC and PSC that host genes involved in innate or acquired immune responses. These loci may provide a clue as to the immune-based pathogenesis of AILD. Moreover, many significant risk loci for PBC and PSC are also risk loci for other autoimmune disorders, such type I diabetes, multiple sclerosis and rheumatoid arthritis, suggesting a shared genetic basis and possibly similar molecular pathways for diverse autoimmune conditions. There is no curative treatment for all three disorders, and a significant number of patients eventually progress to end-stage liver disease requiring liver transplantation (LT). LT in this context has a favourable overall outcome with current patient and graft survival exceeding 80% at 5years. Indications are as for other chronic liver disease although recent data suggest that while lethargy improves after transplantation, the effect is modest and variable so lethargy alone is not an indication. In contrast, pruritus rapidly responds. Cholangiocarcinoma, except under rigorous selection criteria, excludes LT because of the high risk of recurrence. All three conditions may recur after transplantation and are associated with a greater risk of both acute cellular and chronic ductopenic rejection. It is possible that a crosstalk between alloimmune and autoimmune response perpetuate each other. An immunological response toward self- or allo-antigens is well recognised after LT in patients transplanted for non-autoimmune indications and sometimes termed “de novo autoimmune hepatitis”. Whether this is part of the spectrum of rejection or an autoimmune process is not clear. In this manuscript, we review novel findings about disease processes and mechanisms that lead to autoimmunity in the liver and their possible involvement in the immune response vs. the graft after LT.